2019
DOI: 10.1016/j.foodres.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid gels: Influence of oleogel/hydrogel ratio on rheological and textural properties

Abstract: Hybrid gels can be used for controlled delivery of bioactives and for textural and rheological modification of foods. In this regard the hydrogel:oleogel ratio and gel development methodologies showed to be the aspects that influence most of their properties. The present study shows how different fractions of oleogel can influence the hydrogel matrix of an oleogel-in-hydrogel emulsified system in terms of polymorphic arrangement, microstructure, texture and rheology. The hydrogel was prepared by using an aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 29 publications
1
75
0
1
Order By: Relevance
“…Zheng, Mao, Cui, Liu, and Gao (2020) also attributed the increase of the mechanical properties to the role of the oleogel network in the bigel. However, the opposite behavior was observed for sodium alginate hydrogel-beeswax oleogel bigels, where the increase of oleogel fraction disrupted the alginate network and consequently, decreased the mechanical properties (Martins et al, 2019).…”
Section: General Properties Of Bigelsmentioning
confidence: 91%
See 1 more Smart Citation
“…Zheng, Mao, Cui, Liu, and Gao (2020) also attributed the increase of the mechanical properties to the role of the oleogel network in the bigel. However, the opposite behavior was observed for sodium alginate hydrogel-beeswax oleogel bigels, where the increase of oleogel fraction disrupted the alginate network and consequently, decreased the mechanical properties (Martins et al, 2019).…”
Section: General Properties Of Bigelsmentioning
confidence: 91%
“…Guar gum (Sahoo et al, 2015;Vinay K. Singh, Banerjee et al, 2014), gelatin (Sai Sateesh Sagiri, Singh, Kulanthaivel et al, 2015;Satapathy et al, 2015), gelatin-agar mixture (Wakhet et al, 2015), sodium alginate (Rehman, Mohd Amin, & Zulfakar, 2014) starch (Behera, Sagiri, Singh, Pal, & Anis, 2014) and synthetic polymers (PVA and PVP) (Behera, Singh et al, 2015) are examples of hydrocolloids used. In the same way, sorbitan monopalmitate and sunflower oil (Behera, Dey, Sharma, & Pal, 2015), sorbitan monostearate and sesame oil (Vinay K. Singh, Anis et al, 2014;Vinay K. Singh, Banerjee et al, 2014), policosanol from rice bran wax and glyceril stearate with extra virgin olive oil (Lupi et al, 2016) and medium chain triglycerides with beeswax (Martins et al, 2019) were some of the studied organogels.…”
Section: Introductionmentioning
confidence: 87%
“…Formulations that show high viscosity have demonstrated greater resistance to elution and, consequently, they remain longer at the action site [47]. Furthermore, bigels are hybrid gels, and the composition of the systems allows for significant formation of hydrogen bonds mediated by the collective interaction of non-polar and polar constituents of the gel matrix, including sodium alginate (polymer characterized by unique swelling, gelling and mucoadhesive properties) and silica dioxide, thus increasing viscosity and imparting bioadhesive properties [48,49]. On the other hand, the low bioadhesion may be explained on the basis of some studies that concluded that a more rigid polymer network may prevent the proteins present in the biological membrane from interacting with the polymer chain, decreasing the bioadhesive properties of the system [39].…”
Section: Ex Vivo Bioadhesive Propertiesmentioning
confidence: 99%
“…Due to the interest in biodegradable products, hydrogels have been made from natural polymers, such as, starch and CMC 10,11,6,12 . At the same time, composite or mixed hydrogels, constituted by two polymers, are highlighted since the interaction between chains with different structures can improve the material characteristics, enlarging the range of application 3,4 .…”
Section: Introductionmentioning
confidence: 99%